Clinical features, presentation, and tolerance of platinum‐based chemotherapy in germ cell tumor patients 50 years of age and older. Issue 14 (19th April 2013) - Feldman, Darren R.; Voss, Martin H.; Jacobsen, Erin P.; Jia, Xiaoyu; Suarez, J. Andres; Turkula, Stefan; Sheinfeld, Joel; Bosl, George J.; Motzer, Robert J.; Patil, Sujata
Abstract : BACKGROUND: Germ cell tumors (GCTs) primarily affect adolescent and young adult men. Detailed clinical and treatment characteristics in older men are lacking. METHODS: Patients with GCT seen over a 20‐year period at Memorial Sloan‐Kettering Cancer Center were identified. Primary tumor site and histology were compared for patients aged ≥ 50 years at diagnosis versus younger men. For patients aged ≥ 50, individual chart review was performed and treatment delays, changes, and toxicities were recorded for those treated with first‐line chemotherapy. RESULTS: Of 4235 diagnoses of GCT, 3999 (94.4%) were made at age < 50 versus 236 (5.6%) at age ≥ 50. Compared with patients diagnosed before age 50, older men more frequently had seminoma (62.7% versus 36.7%) and less frequently, nonseminoma (34.7% versus 63.2%) ( P  < .0001). Predominant histology switched from nonseminoma to seminoma around age 35. Distribution of primary sites also differed for older versus younger men (testis: 89.4% versus 92.9%; retroperitoneal: 3.8% versus 0.7%; CNS 0% versus 1.7%) except for mediastinal primary tumors, which remained constant across age groups. Fifty patients age ≥ 50 received first‐line platinum‐based chemotherapy; 30 experienced complications leading to treatment discontinuation, delay ≥ 7 days, or regimen change. Twenty‐two (44%) patients experienced neutropenic fever, 6 despite prophylactic growth factor support. Estimated 5‐year survival for chemotherapy‐treated patients was 84.9%. CONCLUSIONS: Men aged ≥ 50 years comprise less than 10% of GCT diagnoses and have distinct clinical and histological characteristics as compared with younger patients. Although complications from chemotherapy occur frequently in older men, prognosis remains excellent when risk‐directed treatment is administered with curative intent. Cancer 2013;119:2574–2581 . © 2013 American Cancer Society . Abstract : Because germ cell tumors are rare in men aged ≥ 50 years, there is limited knowledge regarding the clinical characteristics and outcomes, including treatment tolerability in this population. This retrospective study provides important data on differences in histology and primary tumor site distribution for older versus younger men and details the increased rate of complications that occur in older men with germ cell tumors who are treated with chemotherapy.